2022
DOI: 10.1039/d1ew00903f
|View full text |Cite
|
Sign up to set email alerts
|

Role of natural organic matter and hardness on lead release from galvanic corrosion

Abstract: Suwannee river natural organic matter greatly increased dissolved lead release from galvanic corrosion due to complexation with humic acid-like substances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 55 publications
1
6
0
Order By: Relevance
“…For example, hydroxylpyromorphite (Pb 5 (PO 4 ) 3 (OH)), chloropyromorphite (Pb 5 (PO 4 ) 3 Cl), and phosphohedyphane (Ca 2 Pb 3 (PO 4 ) 3 Cl) have been reported as the potential lead phosphate solids. ,,, The composition of the phosphate-based inhibitors as well as the water chemistry can be the main factors determining the speciation of the lead phosphate solids. The lead phosphate scale formed in this experiment was identified as phosphohedyphane (Ca 2 Pb 3 (PO 4 ) 3 Cl) or a structurally similar phase, which has been reported in other LSLs. ,,, By removing the polyphosphate during treatment stage 2, more lead phosphate solids formed in the bottom layer of the scale. Our study revealed that 0.2 mg/L PO 4 orthophosphate as part of a blend phosphate could thermodynamically promote lead phosphate solid, but the small amount of lead phosphate solid exerted a limited influence on lead release.…”
Section: Resultssupporting
confidence: 70%
“…For example, hydroxylpyromorphite (Pb 5 (PO 4 ) 3 (OH)), chloropyromorphite (Pb 5 (PO 4 ) 3 Cl), and phosphohedyphane (Ca 2 Pb 3 (PO 4 ) 3 Cl) have been reported as the potential lead phosphate solids. ,,, The composition of the phosphate-based inhibitors as well as the water chemistry can be the main factors determining the speciation of the lead phosphate solids. The lead phosphate scale formed in this experiment was identified as phosphohedyphane (Ca 2 Pb 3 (PO 4 ) 3 Cl) or a structurally similar phase, which has been reported in other LSLs. ,,, By removing the polyphosphate during treatment stage 2, more lead phosphate solids formed in the bottom layer of the scale. Our study revealed that 0.2 mg/L PO 4 orthophosphate as part of a blend phosphate could thermodynamically promote lead phosphate solid, but the small amount of lead phosphate solid exerted a limited influence on lead release.…”
Section: Resultssupporting
confidence: 70%
“…And while the seasonal component of the model (Figure b) is described as a function of time (ordinal day), this is a proxy for the physical and chemical inputs that are expected to have caused it. The true seasonal relationship is probably complex and difficult to determine from the study data, but temperature and influent iron concentration are plausible drivers: both varied seasonally and have been shown to impact lead release (Figure b,c). And although dissolved organic carbon has also been shown to increase lead solubility, ,, true colora proxy for dissolved organic carbonwas not strongly seasonal (Figure S9).…”
Section: Resultsmentioning
confidence: 99%
“…Time series representing lead release to drinking water tend to feature extreme values caused by particulate or colloidal lead. Even in 0.45 μm filtrate (i.e., dissolved lead), small colloids can sometimes elevate lead concentrations well above solubility limits . These “outliers” can severely bias parameter estimates unless they are accounted for.…”
Section: Methodsmentioning
confidence: 99%
“…Even in 0.45 µm filtrate (i.e., dissolved lead), small colloids can sometimes elevate lead concentrations well above solubility limits. 48 These "outliers" can severely bias parameter estimates unless they are accounted for.…”
Section: Model Descriptionmentioning
confidence: 99%
“…The true seasonal relationship is probably complex and difficult to determine from the study data, but temperature and influent iron concentration are plausible drivers: both varied seasonally and have been shown to impact lead release (Figure 8b-c). [58][59][60][61] And although dissolved organic carbon has also been shown to increase lead solubility, 48,62,63 true colour-a proxy for dissolved organic carbon 64 -was not strongly seasonal (Figure S9).…”
Section: Identifying Stabilitymentioning
confidence: 99%